Shifts in the soil bacterial community along a salinity gradient in the Yellow River Delta. (30th March 2020) - Zhao, Qingqing; Bai, Junhong; Gao, Yongchao; Zhao, Haixiao; Zhang, Guangliang; Cui, Baoshan
Abstract: Soil salinization has rapidly encroached from the coastline to inland areas over the past two decades in the Yellow River Delta (YRD). Soil samples were collected from low‐ (LSW), medium‐ (MSW), and high‐ (HSW) salinity wetlands at a depth of 0–20 cm for 16S rRNA sequencing and bioinformatic analyses. The richness and α‐diversity indices were significantly lower in saline soils (ECe > 15 dS/m, HSW) than in soils those were not saline (ECe < 15 dS/m, LSW and MSW) ( p  < 0.05), generally showing a decreasing trend with increasing salinities. The phyla, Proteobacteria, Bacteroidetes, Chloroflexi, Acidobacteria and Planctomycetes, represented more than 70% of the bacterial community in the three wetlands, indicating the wide adaption of these phyla to salinity changes. Specifically, Proteobacteria was recognized as the most dominant (35.30% ‐ 38.59%) phylum regardless of salinity. Furthermore, bacterial composition was different among the wetlands, as revealed by β‐diversity indices and analysis of similarities. Linear discriminant analysis (LDA) effect size revealed the presence of 11, 2, and 10 discriminating bacterial taxa (LDA > 4) among LSW, MSW, and HSW, respectively, implying that they can serve as bioindicators of soil salinization. Redundancy analysis, Spearman correlation analysis, and the Mantel test suggested that salinity parameters (EC, Na +, K +, Mg 2+, Ca 2+, Cl −, and SO4 2− ) prominently structured the bacterial community in the current study. These results suggest that the changes of bacterial composition would be induced in these LSW and MSW soils once seawater intrusion occurs.